Pharmacological activation of CB2 receptors counteracts the deleterious effect of ethanol on cell proliferation in the main neurogenic zones of the adult rat brain - Rivera, Patricia; Blanco, Eduardo; Bindila, Laura; Alen, Francisco; Vargas, Antonio; Rubio, Leticia; Pavón, Francisco J.; Serrano, Antonia; Lutz, Beat; Rodríguez de Fonseca, Fernando; Suárez, Juan (Frontiers in Cellular Neuroscience, 2015)
Chronic alcohol exposure reduces endocannabinoid activity and disrupts adult neurogenesis in rodents, which results in structural and functional alterations. Cannabinoid receptor agonists promote adult neural progenitor cell (NPC) proliferation. We evaluated the protective effects of the selective CB1 receptor agonist ACEA, the selective CB2 receptor agonist JWH133 and the fatty-acid amide-hydrolase (FAAH) inhibitor URB597, which enhances endocannabinoid receptor activity, on NPC proliferation in rats with forced consumption of ethanol (10%) or sucrose liquid diets for two weeks. We performed immunohistochemical and stereological analyses of cells expressing the mitotic phosphorylation of histone-3 (phospho-H3+) and the replicating cell DNA marker 5-bromo-2’-deoxyuridine (BrdU+) in the main neurogenic zones of adult brain: subgranular zone of dentate gyrus (SGZ), subventricular zone of lateral ventricles (SVZ) and hypothalamus. Animals were allowed ad libitum ethanol intake (7.3±1.1 g/kg/day) after a controlled isocaloric pair-feeding period of sucrose and alcoholic diets. Alcohol intake reduced the number of BrdU+ cells in SGZ, SVZ and hypothalamus. The treatments (URB597, ACEA, JWH133) exerted a differential increase in alcohol consumption over time, but JWH133 specifically counteracted the deleterious effect of ethanol on NPC proliferation in the SVZ and SGZ, and ACEA reversed this effect in the SGZ only. JWH133 also induced an increased number of BrdU+ cells expressing neuron-specific β3-tubulin in the SVZ and SGZ. These results indicated that the specific activation of CB2 receptors rescued alcohol-induced impaired NPC proliferation, which is a potential clinical interest for the risk of neural damage in alcohol dependence.